IN VITRO ANTIOXIDANT AND PHOTOPROTECTIVE ACTIVITIES OF CARICA PAPAYA FRUITS - SEOW LAY JING; KHOR POH YEN; GOURI KUMAR DASH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to evaluate the antioxidant and photoprotective effects of Carica papaya fruits using spectrophotometric methods. Methods: The dried fruit powder of C. papaya was extracted separately in methanol, ethanol, and distilled water for 2 days on a constant heating water bath at 60°C. The extracts were concentrated under vacuum using a rotary evaporator and separately dried in a desiccator to yield the methanol, ethanol, and aqueous extracts. Proximate analysis of the fruit powder such as determination of ash values, loss on drying, and extractive values was performed as per the World Health Organization guidelines. Total phenolic and flavonoid contents were determined by Folin–Ciocalteu and aluminum chloride methods, respectively. Antioxidant activities of the extracts were evaluated using 2,2-diphenyl-1-picrylhydrazyl radical scavenging method and compared with ascorbic acid. The photoprotective effect was evaluated by the spectrophotometric method. Results: Our results revealed the total phenolic content 59.7±1.15 for methanol extract, 56.1±0.33 for ethanol extract, and 64.4±1.95 for the aqueous extract μg/ml of gallic acid equivalent. The level of flavonoids, expressed in quercetin equivalents in μg/ml, of methanol extract was of 79.3±0.61, ethanol extract 66.3±0.13, and aqueous extract 23.9±0.26, respectively. The free radical scavenging activity of the extracts was found superior to ascorbic acid that was used as the standard for activity comparison. The results of sun protection factor (SPF) in vitro study demonstrated comparable SPF in a concentration-dependent manner. Conclusion: The flavonoids and phenolic compounds present in the extracts could be responsible by the photoprotective effect of C. papaya.